Znaleziska szczątków ludzkich w przestrzeni wczesnośredniowiecznego osiedla w Santoku - Zamelska-Monczak, Kinga; Lorkiewicz-Muszyńska, Dorota (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2025)
The aim of this article is to analyse the human remains obtained during archaeological excavations conducted at an early medieval settlement in Santok. The older stage of the settlement’s existence is attributed to the discovery of human skulls and mandibles. The remains of several children of perinatal age were found in a multi-layered mound located inside the stronghold. The human bone finds presented in this article are not associated with typical early medieval burials and cemeteries. The broad context of these finds is presented in relation to their location and conditions of preservation. An interpretation of the practices of bone deposition and the significance of these assemblages has been suggested.